(untitled) (Superficies y Vacío, 2012)
A study about processing and synthesis by plasma of porous biomaterials based in pyrrole and ethylene glycol is presented. The objective is to obtain porous copolymers with NH and OH groups to be applied as biomaterials. The monomers were copolymerized by resistive glow discharges in a tubular glass reactor at 10-1 mbar and 40-60 W using iodine as dopant and water as oxidant agents. The polymers were obtained as powder and thin films with some pores. The films were swollen with water and subjected to a treatment based on liquid absorption and rapid temperature changes to freeze the liquid trapped in the copolymer. With this procedure new pores were created, some isolated and others interconnected with average diameter between 0.13 µm and 10.75 µm. The morphology was studied by SEM. The results indicate that this material could increase the interaction with cells with the enlarged surface provided by the pores.